Virtual Screening to Identification The Active Compounds from Kratom (Mitragyna speciosa) as Analgetics - Arief, Ihsanul; Inderiyani, Inderiyani (Pharmacon: Jurnal Farmasi Indonesia, 2023)
Kratom (Mytragina speciosa) is one of the endemic plants in Southeast Asia in general and Kalimantan in particular which is proven to have activities as an analgesic, sedative (antidepressant), and, antiobesity, breast anticancer, antinociceptive, CYP450 induction, anti-inflammatory, opiate, antimicrobial, and antioxidant. However, no report states the active compounds from kratom leaves that have these activities. Therefore, this study will identify the active compounds contained in kratom leaves with a virtual screening process responsible for analgesic activity along with the prediction of adsorption, distribution, metabolism, excretion, and toxicity (ADMET) properties. The virtual screening process was performed based on molecular tethering, while the prediction of ADMET properties was done with the help of a web server. The results obtained showed that the compound (-)-epicatechin was most responsible for the analgesic activity of kratom leaves. The ADMET profile of this compound predicts that it has good bioavailability and is non-toxic.